Third molar infections and their impact on systemic health- an awareness study among women degree college students of Udupi City, Karnataka, India - Ananya Prabhu; Ramprasad Vasthare; Prajna P. Nayak; Gargi Gandhi; Shreyosi Banik; Bidisha Sarmah (Journal of Oral Biology and Craniofacial Research)
Introduction: The wisdom teeth usually erupt at the age of 17–25 years leading to the risk of pericoronitis, caries, periodontitis, anterior crowding of teeth and cyst development. Previous studies have reported that the third molar infection is more associated with the age group of 26–35 years and is more commonly reported in the female gender. Aims: Hence, the aim was to assess knowledge regarding third molar infections among women degree college students. Method: ology: This cross-sectional study was conducted among 600 students in three women's degree colleges. Awareness and oral health practices were recorded using a supervised self-administered structured questionnaire. The third molar status was recorded by two calibrated examiners. Descriptive statistics, ANOVA, independent T-test and chi-square tests were used to interpret the data. Results: The prevalence of dental caries and pericoronitis with respect to the third molar was 22.5 % and 10.5 % respectively. 63 % expressed no awareness regarding problems associated with third molars. Only 27.2 % were aware of the impact of third molar infection on general health. Mean awareness score was 3.22 ± 1.60. There was a significant increase in awareness of third molars with age. Presence of dental caries significantly affects knowledge score, with those having dental caries (3.68) having a higher score. Conclusion: This study emphasizes the importance of comprehensive oral health education programs tailored to the needs of students in different educational institutions. By raising awareness about third-molar-related complications and promoting regular dental check-ups, these programs can contribute to improving oral health outcomes among young adults.